Shifting Public Perception in the Jessica Mirna Cyanide-Infused Coffee Case: A Discourse Analysis - Dede Engkis; Ervina CM Simatupang (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2024)
This study aims to investigate the impact of social media on changing public perceptions in the Jessica Mirna Cyanide-Infused Coffee Case. The research method employed is descriptive, with the primary data source from TikTok, the official account @Netflix Indonesia, which released a documentary trailer titled 'Ice Cold: Murder, Coffee, and Jessica Wongso' in September 2023. The study applies Ruth Wodak's Critical Discourse Analysis (CDA) theory along with other social media theories. The utilization of hashtags, trends, and algorithms on social media significantly impacts the broader dissemination of the case, leading to its resurgence in public discourse. Initially, social media was dominated by the hashtag #JusticeForMirna, which later transitioned to #JusticeForJessica following the release of the aforementioned documentary. This analysis also involves understanding language, framing, comments, and public responses, which influence the shaping of public opinion on the case. The research findings highlight shifts in public perception due to the influence of the aforementioned factors and public distrust in the case's transparency, attributed to insufficient evidence in court and newly revealed facts. This has sparked debates and positioned Jessica in two possibilities, either as the perpetrator or as a victim of the justice system. These factors have proven to be crucial in shaping diverse perspectives and generating opinion shifts among the public. Academically, this study provides in-depth insights into the complexity of social media's role in shaping public opinions on controversial issues. This is important given the rapid development of social media and online interactions, emphasizing the transformative power of discourse, narrative framing, and the dynamic nature of public perception